2010
DOI: 10.1590/s1519-69842010000500025
|View full text |Cite
|
Sign up to set email alerts
|

What is the influence of ordinary epidermal cells and stomata on the leaf plasticity of coffee plants grown under full-sun and shady conditions?

Abstract: Stomata are crucial in land plant productivity and survival. In general, with lower irradiance, stomatal and epidermal cell frequency per unit leaf area decreases, whereas guard-cell length or width increases. Nevertheless, the stomatal index is accepted as remaining constant. The aim of this paper to study the influence of ordinary epidermal cells and stomata on leaf plasticity and the influence of these characteristics on stomata density, index, and sizes, in the total number of stomata, as well as the detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 27 publications
1
26
0
7
Order By: Relevance
“…However, for the dry season, the 50% shading level enabled a higher CO 2 assimilation ( Figure 2C). Similar results were obtained by Pompelli et al (2010a) in which the coffee plants grown under 50% shading showed higher photosynthetic rate values compared to plants grown under full sun, during winter conditions. The photosynthetic rate depends on the season, since the low temperatures observed in the dry season can modify the behavior of the coffee plants, decreasing their photosynthetic rates.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…However, for the dry season, the 50% shading level enabled a higher CO 2 assimilation ( Figure 2C). Similar results were obtained by Pompelli et al (2010a) in which the coffee plants grown under 50% shading showed higher photosynthetic rate values compared to plants grown under full sun, during winter conditions. The photosynthetic rate depends on the season, since the low temperatures observed in the dry season can modify the behavior of the coffee plants, decreasing their photosynthetic rates.…”
Section: Resultssupporting
confidence: 86%
“…), indicating that low night temperatures may largely depress in stomatal conductance, even when the daytime temperature is adequate for gas exchange in coffee plants (DaMatta et al, 1997;Ramalho et al, 2003;Silva et al, 2004;Pompelli et al, 2010b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For stomatal density, the same dosage afforded 45.98 mm 2 , not statistically differentiating it from the treatment with alternative means without the addition of the potassium silicate. On the other hand, Pompelli et al (2010) assert that the stomatic index is an intrinsic characteristic of the plant, remaining constant. This information does not apply to treatments performed in this study because there were changes in the stomatic index when potassium silicate was added to the alternative means.…”
Section: Resultsmentioning
confidence: 99%
“…Conditions of water shortages and high light intensity during plant growth resulted in different responses to the varieties of cassava plant. Therefore the cassava plant will make modifications in the form of leaf anatomy stomata density becomes higher, due to surrounding cells that are smaller in size and leaves tend to be thicker (Morais et al, 2004;Pompelli et al, 2010). Tanspiration procces is influenced by a variety of internal factors such as the size of the leaves, the thickness of the leaves, the thickness of the wax layer, and the shape and location of the stomata and external such as; light radiation, temperature, humidity, light, wind and soil water content (Dardjat & Arbayah, 1996;Suyitno & Ratnawati, 2004).…”
Section: Discussionmentioning
confidence: 99%